Evaluation of the effectiveness of an early peripheral burning strategy in controlling wild fires in north-western Zimbabwe - Mapaure, I.; Campbell, Bruce M.; Gambiza, J. (2009)
A review of the occurrence of wild fires in Sengwa Wildlife Research Area (SWRA), Zimbabwe, is presented for the period 1965-1993. The effectiveness and desirability of early burning of peripheral areas introduced in 1979 are evaluated. More than 75% of wild fires occurred between July and October, 48.6% of which originated from communal lands. Early burning of peripheral areas led to significant reductions in extent of areas burnt, from annual mean areas of 115 km2 (1965-1978) to 11 km2 (1979-1993) because of effective control of fires, which originated from communal lands. Some areas did not burn at all after 1979, and the overall probability of burning dropped from 0.484 to 0.187. Whilst it may be desirable to keep fires out of SWRA in the short term, fuel build-ups increase the fire hazard resulting in negative consequences on biodiversity in the long term. Consideration should be given to combine peripheral burning with low-intensity prescribed burning of selected blocks to keep a semblance of natural fire regimes to ensure the maintenance of biodiversity while simultaneously reducing the fire-hazard. An integrated fire management plan should be put in place for SWRA.